OP0274 HPR DEVELOPMENT OF GENERIC CORE COMPETENCES OF HEALTH PROFESSIONALS IN RHEUMATOLOGY: A SYSTEMATIC LITERATURE REVIEW INFORMING THE 2018 EULAR RECOMMENDATIONS. (June 2019) - Fragoulis, George E.; Edelaar, Lisa; Schäfer, Valentin; Schoones, Jan; Iagnocco, Annamaria; Vlieland, Thea Vliet; Nikiphorou, Elena
Abstract : Background: Acquisition and maintenance of competences by Health Professionals in Rheumatology (HPRs) is important to ensure the best care for people with rheumatic and musculoskeletal diseases (RMDs). HPRs' competencies have never been systematically evaluated, nor international recommendations provided. A EULAR Task Force (TF) was formed for this purpose. Objectives: To perform a systematic literature review (SLR) on the core competences of HPRs with a focus on nurses, physiotherapists (PT) and occupational therapists (OT) to inform the "EULAR recommendations for the generic core competences of Health Professionals in Rheumatology" Methods: Thirteen main themes identified by the TF and translated into research questions, formed the basis of the SLR. Existing literature was systematically evaluated using the following databases (PubMed/Medline, Embase, Cochrane library, CENTRAL, Emcare, PsycINFO, Academic Search Premier, Web of Science, Google Scholar, ERIC and National Science Digital Library) from 1/1/1990 to 20/02/2018. Relevant search terms for competences, RMDs and HPRs were used. In addition, EULAR HPR national presidents were invited to share any documents describing HPRs' competences. Inclusion criteria were: studies on competences or roles, knowledge, attitudes, skills or educational needs relevant for the management of people with RMDs, of HPRs in general or specifically of nurses, PTs or OTs, at post-graduate level. Exclusion criteria were: HPRs' competences for children's care or for concurring co-morbidities; extended roles of HPRs; a very specific clinical intervention or an intervention clearly attributable to only one profession or studies written in a language other than English or Dutch. All abstracts were screened to identify eligible studies for full text inclusion. The methodological quality of the studies was scored using appropriate tools (Table). Results: From 591 unique references reviewed, 79 studies were included. Twenty studies addressed competences of multiple HPRs. The methodological quality of most papers was high to medium (Table). The identified studies underpinned a range of HPRs' competences, including: communication skills, promotion of physical activity, basic knowledge about RMDs and education of patients and other health providers. Competences more relevant to specific professions (e.g musculoskeletal system examination skills for PTs and assessment of house and work environment for OTs) were also recorded. Heterogeneity in the HPR desired competences and practice across countries highlighted the need for further education of HPRs to acquire certain competences. Conclusion: High-quality literature is available on the competences of HPRs for the management of people with RMDs. This literature supports the formulation of evidence-based recommendations for the core competences for HRPs by a EULAR Task Force. Disclosure of Interests: None declared